PENGARUH MEDIA INTERNET TERHADAP PRESTASI SISWA-SISWI DI SMA NEGERI 17 MEDAN - Prietsaweny Riris T Simamora (Jurnal Darma Agung, 2019)
This study was conducted by using quantitative correlational method which tests certain theories of methods. This study aims at examining the extent to which variations in a factor are related to others. it was conducted to find whether there is influence between variables and if there are, how close the relationship is close and whether the relationship is meaningful or not. technique in getting the sampling in this study is by total sampling technique in which all the members of population are taken as sampling. In collecting data, researchers used a questionnaire as a data collection tool in this study. Data collected was analyzed using small table analysis, cross table and hypothesis testing using rank spearman. The results show that the influence of internet media on student achievement, this influence was a significant relationship, obtained based on the guilford scale is on a scale that shows a significant relationship. Thus it can be seen that the influence of internet media on student behavior and student achievement is very significant.